Kemampuan Menulis Cerpen dengan Memperhatikan Unsur Intrinsik pada Siswa Kelas X Semester Genap SMK PGRI 2 Bandar Lampung - Hastuti, Hastuti (STKIP PGRI Bandar Lampung, 2020)
The problems raised in this study relate to the ability to write short stories by taking into account the intrinsic elements of the even semester of SMK PGRI 2 Bandar Lampung. Know the causal factors for student difficulties and find out the most prominent difficulties experienced by students. The research method used in order to achieve the research objectives is the quantitative descriptive method. The research population was 125 with a sample of 25. Data collection techniques used short story writing assignment techniques. Data analysis was carried out with quantitative quantitative analysis. Based on the results of data analysis that has been done, it can be concluded that the results of research on cepen's writing ability in class X even semester SMK PGRI 2 Bandar Lampung. Based on seven aspects which are indicators in the study, namely: (1). Theme, (2). Background, (3). Figures and Characterizations, (4). Flow, (5). Point of view, (6). Language style, (7). The mandate shows a pretty good ability. Some students have mastered the procedure for writing short stories quite well. The details are stated that the elements that are expressed incorrectly or each other's mistakes occur include: 1. Flow, 2. Background, 3. Angle of view, 4. Style of language, 5 mandates.